Racial disparities in diabetes prevalence among cancer patients - Ashing, Kimlin Tam; Song, Gaole; Jones, Veronica; Brenner, Charles; Samoa, Raynald (Frontiers in Oncology, 2023)
Cancer inequity is one of the most critical public health issues faced by ethnic minorities and people of lower socioeconomic status. The disparate burden of cancer is caused by poor access to care and inadequate delivery of cancer treatment, as well as comorbid and co-occurring conditions. Diabetes is a common and serious comorbid condition of cancer. To better understand diabetes prevalence among diverse cancer patients, this study analyzed and described characteristics of cancer patients with diabetes from local-level Service Planning Area (SPA) data using City of Hope Comprehensive Cancer Center data, and United States national-level data from The National Health Interview Survey. Results from national level data showed that patients in racial/ethnic minority groups had a higher occurrence of being diagnosed with diabetes, especially for non-Hispanic Blacks (OR=1.76, 95% CI=1.51, 2.03) and Hispanic/Latino individuals (OR=1.34, 95% CI=1.18, 1.52). Cancer patients who are older, ethnic minority, overweight/obese and with lower educational levels were more likely to have co-occurring diabetes. SPA-level patient data found similar results. In response to our findings and other reports, clinicians and health system including health coverage organizations should routinely assess cancer patients for cooccurring chronic illnesses, in particular diabetes. Interventions improving coordinated care that integrates oncology, endocrinology and primary care, targeting cancer patients --especially racial/ethnic minorities, overweight/obese, and older patients who are at increased risk for diabetes -- ought to be considered as best practice Whole Person care. With coordinated care management, ethnic disparities in cancer may be better addressed and reduced. Additionally, policymakers can contribute by enacting policies improving access to and coverage of integrated oncology, chronic disease prevention, and associated specialty care i.e., endocrinology to equalize quality care for ethnic minority, lower educated, overweight/obese and older cancer patients who are more likely to suffer greater comorbidity, and inadequate oncology and coordinated care to reduce disparities.